RIGHT ASCENSIONS OF 200 DOUBLE STARS - Volyanskaya, M. Yu. (Одеські астрономічні публікації, 2017)
This catalogue contains the results of observations of 200 double stars made at Odessa with the Repsold transit circle. The mean epoch of observations is 1986.25, the coordinates are reduced to equinox 2000.0 without taking into account the proper motions. The mean error of catalogue position of RA. is 0.0105. The catalogue corresponds to the FK5 system of stellar places.